2022
DOI: 10.3386/w30799
|View full text |Cite
|
Sign up to set email alerts
|

The Sweet Life: The Long-Term Effects of a Sugar-Rich Early Childhood

Abstract: We show that sugar-rich diet early in life has large adverse effects on the health and economic well-being of adults more than fifty years later. Excessive sugar intake early in life led to higher prevalence of chronic inflammation, diabetes, elevated cholesterol and arthritis. It also decreased post-secondary schooling, having a skilled occupation, and accumulating above median wealth. We identified elevated sugar consumption across lifespan as a likely pathway of impact. Exploiting the end of the post-WWII r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 127 publications
1
5
0
Order By: Relevance
“…Second, we document that fast food access may not only affect health but also cognition, thereby increasing the stakes of a potential lack of counter-measures or regulation of fast food establishments. This extends the literature on the negative consequences of a sugar-rich diet (Gertler and Gracner, 2022) on cognitive outcomes to fast food consumption. Finally, the relative homogeneity of our treatment effects suggests that any interventions or campaigns should target a broad population rather than specific groups e.g., those with a history of obesity in their families (Griffith, 2022).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Second, we document that fast food access may not only affect health but also cognition, thereby increasing the stakes of a potential lack of counter-measures or regulation of fast food establishments. This extends the literature on the negative consequences of a sugar-rich diet (Gertler and Gracner, 2022) on cognitive outcomes to fast food consumption. Finally, the relative homogeneity of our treatment effects suggests that any interventions or campaigns should target a broad population rather than specific groups e.g., those with a history of obesity in their families (Griffith, 2022).…”
Section: Introductionsupporting
confidence: 75%
“…Prior research suggests that proper childhood nutrition could affect education and test scores (see, e.g., Anderson et al, 2018;Bütikofer et al, 2018;Lundborg et al, 2022;Gertler and Gracner, 2022), while some epidemiological studies have attempted to directly link obesity and intelligence (see, e.g., Yu et al, 2010;Belsky et al, 2013). Thus, going beyond health outcomes, we also investigate whether access to fast food restaurants affects cognitive ability.…”
Section: Resultsmentioning
confidence: 99%
“…where cohort=1 if the individual at the time of the 2003 or 2021 interview is 60-64 years old and =0 if the individual is 45-54 years old; scarcity=1 for regions above the 75 th percentile of both proxies of meat scarcity and =0 if below; wave=1 for the 2003 wave and =0 for the 2021 wave of the survey. 39 The coefficient of interest is that of the triple interaction, β 6 . This model allows for differential trends (i) between people of the same age that live in regions that saw severe meat scarcity or not (cohort × scarcity) i,r , (ii) people of the same age who were young children during WWII or who were born afterwards (cohort × wave) i,t , and (iii) people that live in the same region and did or did not experience WWII (scarcity × wave) r,t .…”
Section: Effects On Individual Health Outcomesmentioning
confidence: 99%
“…Our study contributes to such work by being one of the first to show how meat scarcity early in life shapes individual eating habits later on. In a contemporaneous study, Gertler and Gracner (2022) show that exposure to a sugar-rich diet early in childhood impacts health in later life but in this case the main channel is addiction.…”
Section: Introductionmentioning
confidence: 99%
“…A study that took advantage of the end of post-World War II rationing of sugar in 1953 in the United Kingdom showed that excessive sugar intake early in life led to higher rates of chronic inflammation, cholesterol, and arthritis. 109 The researchers were able to take advantage of the fact that sugar intake more than doubled shortly after 1953, whereas consumption of other foods and nutrients around that time stayed relatively constant. Looking for situations like this for which there is a plausibly exogenous source of variation in what individuals are exposed to-such as a change in taxes on sugarsweetened beverages in one municipality compared with another 110 -that affects dietary habits significantly provides important opportunities to learn with quasi-experimental designs.…”
Section: Rigorously Evaluate Ongoing Government Programs and Other Na...mentioning
confidence: 99%